A Sky Full of Stars, Constellations, Satellites and More! Legal Issues for a ‘Darkʼ Sky - Steven Freeland; Anne-Sophie Martin (Oslo Law Review)
An ever-increasing number of actors, including private entities, are conducting space activities that involve the launch of spacecraft into orbit. The ‘miniaturisationʼ of technology has meant that this now includes the launch of large constellations of small satellites. Notwithstanding their commercial benefits, the deployment of large numbers of objects into Low Earth Orbit raises concerns for elements of the international space community specifically concerned with the protection of the ‘darkʼ skies. Large constellation programmes and space debris reflect sunlight into astronomical telescopes or cross their field of view, in many instances degrading certain astronomical observations which would otherwise support our capacity to understand the universe, enable deep-space navigation and exploration and provide early warning detection of near-Earth objects. The various differing interests at stake represent challenges in the application of international environmental law as well as for the current space legal framework, especially for the preservation of the space environment and the long-term sustainability of space activities. Considering the congested space environment and the need to preserve the ‘darkʼ skies for astronomical observation, establishing space traffic management rules and standards is of particular importance.